Spontaneous Hepatic Rupture in Amyloidosis – Report of a Case - Lehmann, T. G.; Scheble, V.; Miller, S.; Heininger, A.; Fend, F.; Koenigsrainer, A. (Zeitschrift für Gastroenterologie, 2012)
In systemic amyloidosis spontaneous rupture of the liver is a rare complication. Here we report on a patient with unrecognized systemic amyloidosis who presented to an outside hospital with unspecific abdominal pain. Under the signs of a hemorrhagic shock, distended abdomen and intraabdominal bleeding a laparotomy was performed. Due to uncontrollable hemorrhage of the ruptured right liver lobe a packing was performed. After being transferred to the reporting institution a CT scan was performed showing a grade IV laceration of the right liver. Therefore a transarterial embolization of the right hepatic artery was carried out. The following day an infection of the abdominal cavity and the abdominal wall with gas-producing bacteria was noticed and a relaparotomy, necrectomy and repacking due to diffuse bleeding were performed. The situation deteriorated and at the second relaparotomy the following day an almost completely necrotic liver was found. The patient deceased the following day. Life-threatening spontaneous liver rupture due to systemic amyloidosis might only successfully be cured by high urgency liver transplantation as presented in the literature. However, in two published cases interventional therapy by embolization of bleeding vessels has saved patients’ life.
Keywords: hepatic rupture; amyloidosis; liver embolization; liver packing